Self-expandable metallic stent as a rescue therapy in stenotic Crohn’s Disease - Erkin Öztaş; Muhammet Yener Akpınar; Yasemin Özderin Özin; Selçuk Dişibeyaz (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Öztaş E, Akpınar MY, Özderin Özin Y, Dişibeyaz S. Self-expandable metallic stent as a rescue therapy in stenotic Crohn’s Disease. Turk J Gastroenterol 2019; 30(4): 381-2.